Environmentally friendly biological nanofibers based on waste feather keratin by electrospinning with citric acid vapor modification. Issue 18 (2nd December 2020) - Ding, Jiao; Lai, Ruihao; Chen, Wenjie; He, Ming; Zhu, Guodian; Huang, Suqing; Yin, Guoqiang
Abstract: Waste feather keratin (FK)‐based nanofibers by electrospinning and citric acid (CA) vapor modification has been successfully prepared and investigated. FK, poly(vinyl alcohol), and poly(ethylene oxide) have been used as raw materials and CA vapor as cross‐linker. The structural, thermal, hydrophobicity, and mechanical properties of FK‐based nanofibers by CA vapor modification with various cross‐linking time have been completely explored. In order to investigate the effect of H2 O vapor on CA vapor modification, H2 O vapor modification was performed on the FK‐based nanofibers at the same conditions. The results show that the average diameter of nanofibers increased from 250.83 ± 29.65 nm to 338.79 ± 31.43 nm by CA vapor modification with 15 h. Similarly, the thermal stability and water resistance of FK‐based nanofibers by CA vapor modification have been significantly improved. The tensile strength ( σ b ) and elongation at breakage point ( ε b ) of FK‐based nanofibers after CA vapor modified for 15 h were about 1.5 and 2 times higher than that of nonmodified nanofibers, respectively. By comparison, scanning electron microscopy results suggest that the FK‐based nanofibers modified by H2 O vapor cannot maintain the morphology of the nanofibers, resulting in large‐scale adhesion. The thermal properties of FK‐based nanofibers with H2 O vapor modification have no obvious change. The hydrophobicity and mechanical properties of FK‐based nanofibers by H2 O vapor modification are not as good as that of CA vapor modification. In summary, these results exhibit that nontoxic and natural CA can be used as cross‐linking agent to enhance the comprehensive performance of FK‐based nanofibers. This study provides a new method to modify FK‐based nanofibers and refined the waste feathers, which not only protected the environment, but also gained benefits, which has a broad application prospect. Abstract : Non‐toxic and natural CA can be used as cross‐linking agent to enhance the comprehensive performance of waste feather keratin‐based nanofibers. This study provides a new method to modify nanofibers and refined the waste feathers, which not only protected the environment, but also gained benefits, which has a broad application prospect.